Determinación de la incidencia de las principales plagas de la caña de azúcar (Saccharum spp.) en el cantón Pangua, Provincia Cotopaxi. - Ulloa Briones, Mayra Carolina (2016)
In the canton Pangua there are a large number of families that are dedicated to the cultivation of sugar cane to obtain its derivatives, especially panela and alcohol; However, little is known about the phytosanitary problems affecting the crop in this area and its effects on the production and yield of the same. Under these circumstances, the research was aimed at determining the incidence of the main pests of sugarcane in the Pangua area, in the province of Cotopaxi. Given the agroclimatic characteristics of the area under study, a stratification was made in three zones: low, medium and high. The low zone comprises of 300 to 600 meters on the level of sea (msnm), the average zone between 800 and 1100 msnm and the high zone between 1350 and 1500 msnm. In each area 10 farms were randomly taken and 10 sampling sites were taken inside each farm. At the sampling site, the percentage of infestation (% I) and percentage of infestation intensity (% II) caused by stalk borer, Diatraea saccharalis, striped weevil, Metamasius hemipterus, and giant borer, Telchin ( = Castnia) licus. In addition, the percentage of shoots of spittle infested stems, Mahanarva andigena, and the number of large nymphs, small and adult by shoot or stem were evaluated. Of the species of borers evaluated, the highest incidence in the three zones corresponded to the striped weevil, M. hemipterus, with 6.3, 4.9 and 4.9% I. And, 0.51, 0.49 and 0.46% II, in the Medium, high and low areas, respectively. Regarding D. saccharalis, the highest level of infestation and infestation intensity occurred in the upper zone, with 4.7%. And 0.60% I.I; Whereas, for T. licus the highest incidence was presented in the lower zone, with 1.0% I. And 0.09% I.I. In relation to salivazo, the highest incidence is in the middle zone, with an average of 64% of infested outbreaks and a population of 18.4, 15.8 and 13.0 small nymphs, large nymphs and adults for every 10 Outbreaks, respectively. According to these results, the intensity levels of infestation and damage caused by the three insect species are well below the level of economic damage established for these insects in sugarcane (5% I.I.). While in the case of spittlebug the levels of infestation would be around the economic bones established for this species of pest.